Pelatihan Penulisan Karya Tulis Ilmiah Untuk Meningkatkan Profesionalisme Anggota MGMP PPKn SMA Negeri Dan Swasta Kota Surabaya - Suhartono, Suhartono; Dwi Retnani Srinarwati; Maya Mustika Kartika Sari; Neneng Rika Jazilatul Kholidah; Titis Nurrusama Nilakandi; Rahmatul Imaniar; Erdianto Widogo (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
The activity of writing scientific papers, especially scientific articles, is one of the activities that must be done by professional teachers. Apart from being a professional demand, writing scientific papers for teachers is also a form of scientific implementation and dissemination to the community. The purpose of this training activity is expected to improve the ability to write scientific papers, especially scientific articles for teachers. The method of implementing this training is divided into three stages. First, the presentation of the material, the two participants were divided into groups to discuss things that could be raised as the theme of writing scientific articles, the third practice in groups with the guidance of lecturers of the PPKn study program, Faculty of Teacher Training, PGRI Adi Buana University, Surabaya, and assistance to complete activities synchronously and asynchronously. This training resulted in 9 scientific articles that have been worked on by teacher groups, three of which are the results of the implementation of classroom action research (PTK) that has been previously carried out by teachers, and there are two participant articles that have been successfully uploaded to the national online journal Pacivic Universitas PGRI Adi Buana Surabaya.